Female participation in Judean family religions : an archaeological perspective towards a heterarchical understanding - Bosman, Hendrik L. (Stellenbosch Theological Journal, 2022)
In this contribution it will be argued that females in ancient Judean families not only played economic, educational, reproductive, and sexual roles, but also took part in religious activities performed within the extended family; and that this neglected religious role of females must be taken into consideration when reflecting on the status of females within the male-dominated beit `ab ("house of the father" or extended family). The possible role played by females in ancient "family religion" will be investigated by engaging with the research related to Judean Pillar Figurines and the role of the queen mother in Judean royal households. Against this background, it will be argued that it is possible that ancient Judahite families had heterarchical qualities despite their dominant hierarchical and patriarchal character in view of the religious agency of women suggested by archaeological evidence.